Dampak Pernikahan Dini Pada Generasi Z Dalam Pencegahan Stunting - Maiza Duana; Siti Maisyaroh Fitri Siregar; Sufyan Anwar; Jun Musnadi; Arfah Husna; Lili Eky Nursia N (Asosiasi Dosen Akuntansi Indonesia, 2022)
The results of the study, WHO said, one of the problems of stunting was due to the high rate of early marriage. the proportion of women aged 20-24 years who are married is higher than Indonesia's figure of 5.43 and 4.60 in 2021. This community service is carried out to provide education about stunting prevention through increasing the age of marriage. The method used in determining the target is the invitation to youth numbers in the Teuku Umar University campus environment by presenting health cadres and participation from the West Aceh Women's Empowerment and Child Protection Service (DP3AD). The activity was assisted by students who are members of the Information and Youth Counseling Center (PIK-R) of Teuku Umar University. Research shows that the earlier the mother gets married, the higher the percentage of children and their malnutrition. Based on these problems, it is necessary to conduct socialization with community service activities for Generation Z to maximize knowledge about the early impact of stunting. The enthusiasm of the participants was seen in the increase in participants' knowledge after participating in the service.